Strengths-based approaches to crime and substance use: from drugs and crime to desistance and recovery - Best, David (Routledge, Taylor & Francis Group, 2020)
Although there is a strong and growing literature in the two areas of desistance and addiction recovery, they have developed along parallel pathways with little systematic assessment of the empirical evidence about the co-occurrence of the relationship or how one area can learn from the other. This book aims to fill that gap by bringing together emerging literature on the relationship between offending and substance use. Instead of focusing on the active period of its onset and persistence, this book examines the mechanisms that support desistance, addiction recovery, and the common themes of reintegration and rehabilitation. With contributions from a wide range of international experts in the fields of desistance and addiction recovery, the book focuses on a strengths-based, relational and community-focused approach to long-term change in offending and drug-using populations, as well as the shared barriers to effective reintegration for both. This book will be highly informative for a wide audience, from academics and students interested in studying desistance and recovery to those working in addiction services and the criminal justice system as well as policy makers and the people undertaking their own journeys to desistance and recovery